Βιβλιοκρισία: Round Trip to Hades in the Eastern Mediterranean Tradition. Visits to the Underworld from Antiquity to Byzantium. Edited by G. EKROTH and I. NILSSON [Cultural Interactions in the Mediterranean 2], Leiden 2018. - ΛΑΜΠΑΚΗΣ, Στυλιανός (Byzantina Symmeikta, 2020)
Βιβλιοκρισία: Round Trip to Hades in the Eastern Mediterranean Tradition. Visits to the Underworld from Antiquity to Byzantium. Edited by G. Ekroth and I. Nilsson [Cultural Interactions in the Mediterranean 2], σελ. xviii+ 398, Leiden 2018.